Poor Tuberculosis Treatment Outcomes Associated with Older Age, Previous Treatment, HIV and Drug Resistance at Seven Hospitals in Indonesia - Dona Arlinda; Retna Mustika Indah; Aris Yulianto; Agus Dwi Harso; Armaji Kamaludi Syarief; Muhammad Karyana (Jurnal Penelitian dan Pengembangan Pelayanan Kesehatan, 2020)
Abstract Indonesia is a high burden country for tuberculosis (TB), multidrug-resistant (MDR) TB, and TB-HIV. We aimed to determine factors associated with poor TB treatment outcomes. A hospital-based TB Registry at seven referral hospitals in Java and Bali included data from patients aged ≥15 years who were diagnosed with TB from 1 January 2014 - 31 December 2015. The factors were assessed by logistic regression. From 2,051 TB patients, 1,180 (57.5%) were male and median age was 38 years (IQR 27-50 years), 452 (22%) had previous TB treatment history, 1,447 (70.6%) had pulmonary TB, 216 (10.5%) TB-HIV, 296 (14.4%) TB-DM and 248 (12.1%) were resistant to ≥1 anti-TB drug. Treatment outcome was unknown for 135 (6.6%) subjects and 1,137 (55.4%) who were still on treatment. Among the 779 with available outcome, 358 (46%) were treatment success, 248 (31.8%) transferred out, 112 (14.4%) defaulted, 46 (5.9%) died and 15 (1.9%) failed. After controlling other factors, poor TB treatment was associated with age ≥38 years (p=0.003; aOR 1.58; 95% CI 1.2-2.1), previous history of TB treatment (p<0.001; aOR 2.55; 95% CI 1.5-4.2) and resistance to ≥1 anti-TB drug (p<0.001; aOR 11.66; 95% CI 3.8-36.1). Mortality was associated with previous history of TB treatment (p=0.003; aOR 3.87; 95% CI 1.7-9.6), TB-HIV (p=0.001; aOR 10.43; 95% CI 4.2-26.1), and resistance to ≥1 anti-TB drug (p=0.001; aOR 9.48; 95% CI 2.6-34.0). Treatment in TB patients with older age, history of previous TB treatment, HIV, and drug resistance should be closely monitored. Keywords: Indonesia, tuberculosis, treatment outcome Abstrak Indonesia adalah negara dengan beban tinggi untuk tuberkulosis (TB), TB resisten obat (MDR) dan TB-HIV. Analisis ini bertujuan untuk menentukan faktor yang terkait dengan luaran pengobatan TB yang buruk. Registri TB berbasis rumah sakit di tujuh rumah sakit rujukan di Jawa dan Bali mencakup data dari pasien berusia ≥15 tahun yang didiagnosis TB dari 1 Januari 2014 - 31 Desember 2015. Faktor-faktor tersebut dinilai dengan regresi logistik. Dari 2.051 pasien TB, 1.180 (57,5%) laki-laki dan median usia 38 tahun (IQR 27-50 tahun), 452 (22%) memiliki riwayat pengobatan TB sebelumnya, 1.447 (70,6%) memiliki TB paru, 216 (10,5%) TB-HIV, 296 (14,4%) TB-DM dan 248 (12,1%) resisten terhadap ≥1 obat anti-TB. Luaran pengobatan TB tidak diketahui untuk 135 (6,6%) subjek dan 1.137 (55,4%) yang masih dalam pengobatan. Di antara 779 dengan luaran pengobatan diketahui, 358 (46%) pengobatan berhasil, 248 (31,8%) pindah, 112 (14,4%) putus pengobatan, 46 (5,9%) meninggal dan 15 (1,9%) gagal. Setelah dikontrol terhadap faktor lain, luaran pengobatan TB yang buruk dikaitkan dengan usia ≥38 tahun (p = 0,003; aOR 1,58; 95% CI 1,2-2,1), riwayat pengobatan TB sebelumnya (p <0,001; aOR 2,55; 95% CI 1,5-4,2) dan resistansi terhadap ≥1 obat anti-TB (p <0,001; aOR 11,66; 95% CI 3,8-36,1). Kematian dikaitkan dengan riwayat pengobatan TB sebelumnya (p = 0,003; aOR 3,87; 95% CI 1,7-9,6), TB-HIV (p = 0,001; aOR 10,43; 95% CI 4,2-26,1), dan resistansi terhadap ≥1 anti -TB obat (p = 0,001; aOR 9,48; 95% CI 2,6-34,0). Pengobatan pada pasien TB dengan usia yang lebih tua, riwayat pengobatan TB sebelumnya, HIV dan resistansi obat harus dipantau secara ketat. Kata kunci: Indonesia, tuberkulosis, luaran pengobatan